EXPERIMENTAL ANIMAL MODELS OF PARKINSON’S DISEASE: AN OVERVIEW - IMRAN, MOHD; MISHRA, ANURADHA; USMANI, AFREEN; EQBAL, ASIF (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Parkinson’s disease (PD) is the 2nd most common neurodegenerative disorder due to gradual loss of dopaminergic nerves in the substantia nigra in the midbrain which leads to motor symptoms: For instance, gait dysfunction, involuntary tremor, rigidity, and progressive postural instability. PD has no cure and available current treatment is only symptomatic. At present, the main treatment of PD relies on Levodopa that slowing down the disease development to some level but can lead to several side effects. The literature confirms the available models of Parkinsonism that is chemical-induced, that is, by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine and 6-hydroxydopamine-induced Parkinsonism furthermore transgenic models linked to monogenic alterations in SNCA, LRRK2, UCH-L1, PRKN, and PINK1 genes. In this review article, we conclude that the presently available neurotoxic models of PD that offer a platform for neuroprotective drug discovery.